Status Hak Waris Perkawinan Beda Agama di Indonesia Perspektif Yuris Islam Klasik Dan Kontemporer - Tohari, Ilham; Hazyimara, Karunia (Peradaban Journal of Law and Society, 2023)
This research aims to investigate the inheritance status of interfaith marriages in Indonesia's multicultural basis according to classical and contemporary jurisprudence. The method used is library research with a descriptive-qualitative approach. The results of the research are that multicultural-based fiqh can be understood through the reinterpretation of religious texts using the maqashid sharia approach. Interfaith marriage as one of the effects of social interaction in a multicultural country still leads to a taboo understanding that interreligious marriage in Indonesia is not allowed, as classical and contemporary jurist opinion generally forbids it. Questioning the status of inheritance in interfaith marriages, the scholars of the four schools of thought, Ali as-Shabuni, Sayyid Sabiq, Muhammad as-Syaukani, and Mustafa as-Salabi agreed that their inheritance rights were hindered, while according to the Imami school of thought, Ibn Taimiyah and Ibn Qayyim al-Jauzi and Yusuf Al- Qardhawi was not deterred by the pretext of helping each other. In Indonesia, the inheritance rights of interfaith marriages are discussed in the decision of the Supreme Court (MA) No. 368K/AG/1995 and the decision of the Supreme Court of the Republic of Indonesia Number 51K/AG/1999 which shows that in terms of not obtaining inheritance rights, they will receive a "wasiat wajibah". Kajian ini bertujuan untuk mengeksplorasi gagasan status waris perkawinan beda agama di basis multikultural Indonesia menurut yuris klasik dan yuris kontemporer. Metode yang digunakan adalah metode kepustakaan (library research) dengan pendekatan deskriptif-kualitatif. Adapun hasil dari penelitian adalah fikih berbasis multikultural dapat difahami melalui reintepretasi teks agama menggunakan pendekatan maqashid syariah. Perkawinan beda agama sebagai salah satu dampak interaksi sosial di negara multikultural masih mengantarkan pada pemahaman yang tabu sehingga perkawinan beda agama di Indonesia tidak diperbolehkan, sebagaimana pendapat yuris klasik dan kontemporer yang secara umum mengharamkannya. Menyoal status waris dalam perkawinan beda agama ulama empat mazhab, Ali as-Shabuni, Sayyid Sabiq, Muhammad as-Syaukani dan Musthafa as-Salabi sepakat bahwa hak warisnya terhalang sedangkan menurut mazhab Imamiyah, Ibnu Taimiyah dan Ibnu Qayyim al-Jauzi serta Yusuf Al-Qardhawi tidak terhalang dengan dalih semangat tolong-menolong. Di Indonesia, terkait hak waris perkawinan beda agama dibahas pada putusan Mahkamah Agung (MA) No.368K/AG/1995 dan putusan Mahkamah Agung RI Nomor 51K/ AG/1999 yang menunjukkan bahwa secara istilah tidak mendapat hak waris tetapi akan mendapat wasiat wajibah.